EnanDIM - a novel family of L-nucleotide-protected TLR9 agonists for cancer immunotherapy. Issue 1 (8th January 2019) - Kapp, Kerstin; Volz, Barbara; Curran, Michael A.; Oswald, Detlef; Wittig, Burghardt; Schmidt, Manuel
Abstract : Background: Toll-like receptor 9 agonists are potent activators of the immune system. Their clinical potential in immunotherapy against metastatic cancers is being evaluated across a number of clinical trials. TLR9 agonists are DNA-based molecules that contain several non-methylated CG-motifs for TLR9 recognition. Chemical modifications of DNA backbones are usually employed to prevent degradation by nucleases. These, however, can promote undesirable off-target effects and therapeutic restrictions. Methods: Within the EnanDIM® family members of TLR9 agonists described here, D-deoxyribose nucleotides at the nuclease-accessible 3′-ends are replaced by nuclease-resistant L-deoxyribose nucleotides. EnanDIM® molecules with varying sequences were screened for their activation of human peripheral blood mononuclear cells based on secretion of IFN-alpha and IP-10 as well as activation of immune cells. Selected molecules were evaluated in mice in a maximum feasible dose study and for analysis of immune activation. The ability to modulate the tumor-microenvironment and anti-tumor responses after EnanDIM® administration was analyzed in syngeneic murine tumor models. Results: The presence of L-deoxyribose containing nucleotides at their 3′-ends is sufficient to prevent EnanDIM® molecules from nucleolytic degradation. EnanDIM® molecules show broad immune activation targeting specific components of both the innate and adaptive immune systems. Activation was strictly dependent on the presence of CG-motifs, known to be recognized by TLR9. The absence of off-target effects may enable a wide therapeutic window. This advantageous anti-tumoral immune profile also promotes increased T cell infiltration into CT26 colon carcinoma tumors, which translates into reduced tumor growth. EnanDIM® molecules also drove regression of multiple other murine syngeneic tumors including MC38 colon carcinoma, B16 melanoma, A20 lymphoma, and EMT-6 breast cancer. In A20 and EMT-6, EnanDIM® immunotherapy cured a majority of mice and established persistent anti-tumor immune memory as evidenced by the complete immunity of these mice to subsequent tumor re- challenge. Conclusions: In summary, EnanDIM® comprise a novel family of TLR9 agonists that facilitate an efficacious activation of both innate and adaptive immunity. Their proven potential in onco-immunotherapy, as shown by cytotoxic activity, beneficial modulation of the tumor microenvironment, inhibition of tumor growth, and induction of long-lasting, tumor-specific memory, supports EnanDIM® molecules for further preclinical and clinical development.